2010
DOI: 10.5714/cl.2010.11.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing on Morphology, Electrical Conductivity and Flexural Properties of Exfoliated Graphite Nanoplatelets-Polyamide Nanocomposites

Abstract: Graphene is one of the most promising materials for many applications. It can be used in a variety of applications not only as a reinforcement material for polymer to obtain a combination of desirable mechanical, electrical, thermal, and barrier properties in the resulting nanocomposite but also as a component in energy storage, fuel cells, solar cells, sensors, and batteries. Recent research at Michigan State University has shown that it is possible to exfoliate natural graphite into graphite nanoplatelets co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…This increase was taken to be an indication of an increasing nucleating efficiency with the addition of GNPs to the PP matrix, as reported elsewhere . A sharp peak around 26.5° appearing for the PP/GNPs nanocomposites was assigned to the graphene (002) diffraction peak . In a comparison of the XRD patterns of the PP/GNPs nanocomposites prepared by the die with and without shunt plates, we observed that the (002) diffraction peak intensity of the nanocomposites prepared by the die with shunt plates was stronger than that by the die without shunt plates.…”
Section: Resultssupporting
confidence: 74%
“…This increase was taken to be an indication of an increasing nucleating efficiency with the addition of GNPs to the PP matrix, as reported elsewhere . A sharp peak around 26.5° appearing for the PP/GNPs nanocomposites was assigned to the graphene (002) diffraction peak . In a comparison of the XRD patterns of the PP/GNPs nanocomposites prepared by the die with and without shunt plates, we observed that the (002) diffraction peak intensity of the nanocomposites prepared by the die with shunt plates was stronger than that by the die without shunt plates.…”
Section: Resultssupporting
confidence: 74%
“…The sharp peak around 17.1° appears for the PP/GNPs nanocomposites is the PP (040) diffraction peaks. While the sharp peak around 26.5° can be assigned to the graphene (002) diffraction peak , whose obvious increase can be attributed to the increasing of GNPs. Comparing the XRD patterns of PP/GNPs nanocomposites extruded without and with ultrasound treatment, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many research efforts have been devoted to studying the effect of carbon nanoparticles, such as xGNP and carbon nanotubes, on the mechanical, thermal, and/or electrical properties of various polymers [80][81][82][83][84][85][86][87][88]. Fig.…”
Section: Effect Of Xgnp On the Electrical Resistivity Of Peti-5 [80]mentioning
confidence: 99%